Infecciones de transmisión sexual y embarazo en pacientes atendidas en el Centro de Salud Universitario de Motupe - Buri Guachisaca., Maribel Alexandra (2023)
Sexually transmitted infections (STIs) constitute an epidemic in most countries, young people are the most vulnerable population to suffer and transmit STIs, they occupy the second place in order of importance in the general morbidity of women between 15 and 44 years. The purpose of the present investigation was to identify the presence of STIs, to know the complications and to establish the relationship between the type of STI and the complications in pregnant women at the Motupe University Health Center in the period 2016-2021 according to age group and pregnancy trimester. A quantitative, descriptive and cross-sectional study was carried out, in a population of 250 pregnant women, for which the clinical histories were reviewed, data that allowed the filling of the data collection form, after analyzing it was observed that 94% (n=234) were carriers of a clinically diagnosed STI in 31.6% (n=79) aged 20-24, 21.2% (n=53) aged 25-29, and 15.6% (n=39) from 30-34 years. Of the pregnant women with STIs, 11.6% (n= 29) presented complications, mainly premature rupture of membranes and threat of preterm labor. When relating the variables by calculating the Chi square with a value of p: 0.9591 no there was a statistically significant relationship, there was a high percentage of STIs in pregnant women, Chlamydia was the most prevalent, followed by Trichomonas and genital herpes